Canine echinococcosis: genetic diversity of Echinococcus granulosus sensu stricto (s.s.) from definitive hosts. Issue 6 (November 2015) - Boufana, B.; Lett, W.; Lahmar, S.; Griffiths, A.; Jenkins, D.J.; Buishi, I.; Engliez, S.A.; Alrefadi, M.A.; Eljaki, A.A.; Elmestiri, F.M.; Reyes, M.M.; Pointing, S.; et al.
Abstract Canids, particularly dogs, constitute the major source of cystic echinococcosis (CE) infection to humans, with the majority of cases being caused by Echinococcus granulosus (G1 genotype). Canine echinococcosis is an asymptomatic disease caused by adult tapeworms of E. granulosus sensu lato (s.l.). Information on the population structure and genetic variation of adult E. granulosus is limited. Using sequenced data of the mitochondrial cytochrome c oxidase subunit 1 (cox1) we examined the genetic diversity and population structure of adult tapeworms of E. granulosus (G1 genotype) from canid definitive hosts originating from various geographical regions and compared it to that reported for the larval metacestode stage from sheep and human hosts. Echinococcus granulosus (s.s) was identified from adult tapeworm isolates from Kenya, Libya, Tunisia, Australia, China, Kazakhstan, United Kingdom and Peru, including the first known molecular confirmation from Gaza and the Falkland Islands. Haplotype analysis showed a star-shaped network with a centrally positioned common haplotype previously described for the metacestode stage from sheep and humans, and the neutrality indices indicated population expansion. Low Fst values suggested that populations of adult E. granulosus were not genetically differentiated. Haplotype and nucleotide diversities for E. granulosus isolates from sheep and human origin were twice as high as those reported from canid hosts. This may be related to self-fertilization of E. granulosus and/or to the longevity of the parasite in the respective intermediate and definitive hosts. Improved nuclear single loci are required to investigate the discrepancies in genetic variation seen in this study.